Assessing the strength and weakness of the dataarts cultural data profile in comparison with the nccs 990 data. Issue 3 (1st March 2016) - Kim, Mirae; Charles, Cleopatra
Abstract : The DataArts dataset, although it covers mostly arts organizations, has emerged as an alternative source of data for nonprofit research. Most existing studies use the IRS 990 data, which is considered a reliable source for research. We evaluate the reliability of the DataArts dataset by comparing the consistency of the values reported to the DataArts Cultural Data Profile (CDP) and to the 990 forms. We: 1) examine correlations between the same measures in each dataset, 2) assess the cumulative distribution of differences between the two datasets and 3) compare the results of the same empirical model conducted with the DataArts dataset and 990 data, respectively. We conclude that the DataArts dataset is an adequate and reliable source of financial and performance information, but researchers should be aware of a few limitations.